Effects of spall edge profiles on the edge plastic deformation for a roller bearing. (May 2019) - Liu, Jing; Shi, Zhifeng; Shao, Yimin; Xiao, Huifang
A clear understanding of the plastic deformations at the spall edges is a primary task for the edge propagation predictions in rolling element bearings. This work proposed an elastic–plastic two-dimensional finite element model for calculating the contact stress and plastic deformation between the rolling element and raceway. This model includes a rolling element and one raceway. The rectangular plane strain solid elements are used to formulate the finite element model. The Coulomb model is used to formulate the friction force between the rolling element and raceway. A bilinear kinematic hardening material model is used in the finite element model, which can formulate the elastic–plastic deformations. The studied spall edge profiles are assumed to be sharp and cylindrical ones. To validate the finite element model, the contact deformations between the rolling element and the raceway from the proposed model and Hertzian contact theory are compared. Effects of spall edge profiles on the edge plastic deformations at the edge are analyzed, as well as the edge plastic deformation zone width. Based on the numerical results, the relationship between the edge plastic deformation and the spall edge profile, and that between the edge plastic deformation zone width and the spall edge profile are established. The results show that the edge plastic deformation is significantly influenced by the spall edge profiles, as well as the edge plastic deformation zone width. This paper provides a clear understanding of the effects of the edge profiles on the plastic deformations and propagation at the spall edge.